All in the Details: A First Assessment for the Viability of Metabarcoding in Diet Composition Analysis of African Wild Dogs (Lycaon pictus) - Bridget C. O'Connor; Bruce Crossey; Grant Hall; Andre Ganswindt; Carel J. Oosthuizen (Ecology and Evolution)
ABSTRACT DNA metabarcoding is a contemporary technique in diet composition studies and stands to fill key knowledge gaps left by traditional diet analysis methods. For endangered species such as the African wild dog (Lycaon pictus), the fulfilment of these knowledge gaps presents an opportunity for improved management practices and vulnerability assessments. There are an estimated ~600 African wild dogs remaining in South Africa. These dogs are generally understood to prey upon impala (Aepyceros melampus) and other medium‐sized ungulates. Here, we present the first assessment of DNA metabarcoding as a valuable method for diet composition analysis of this highly social carnivore. DNA from faecal samples collected across seven landscape types in the Kruger National Park (KNP) was extracted and used to determine the presence of seven unique prey taxa, including novel species such as the Cape hare (Lepus capensis). Impala was identified as a prey item in all landscape types, complementing the diet preference prediction made with stable isotope analysis using the same samples and existing understanding of wild dog diet. Given recommended improvements, the application of DNA metabarcoding in wild dog diet analysis shows promising prospects for identifying novel prey species and validating previous records of this endangered canids diet.